KAMPUNG RAMAH ANAH GENDENG SEBAGAI ALTERNATIF PEMENUHAN HAK BERKEMBANG PADA ANAK USIA DINI - Jazariyah, Jazariyah (Program Studi Pendidikan Guru Raudlatul Athfal, UIN Sunan Kalijaga Yogyakarta, 2016)
This article is intented to uncover the importance of environmental explroration for children. One example is child-friendly environment which is also a special effort from government. They set out in minister of women’s empowerment Republic of Indonesia with PP No 2 Tahun 2009 about child-friendly city (CFC). The result shows that Kampung Ramah Anak Gendeng is one of community efforts to fulfill the right of grow and develop on early childhood. Many programs that held on Kampung Ramah Anak Gendeng, such as children community, bimbingan belajar and TPA (Taman Pendidikan AL Qur’an). Factors that support child-friendly environment on Gendeng are Public awareness about the importance of early childhood development and continuity on socializing the importance of early childhood development. Barrier Factors on implementasion of child-friendly environment on Gendeng are lack of fund to held the program of Kampung Ramah Anak on Gendeng and lack of monev (monitoring and evaluation) from government.